The The Uncertainty of Essential Oil as a Cosmetic Product Market: A Market Sociology Perspective - Syifa Andini Salsabila (International Journal of Social Science and Business, 2023)
Essential oil as a cosmetic product is believed to be one of the highest-demand commodities, especially when the back to nature is the current leading trend. However, the essential oil market itself faced an uncertain future. The uncertainty problem in this market can be seen from the fluctuating prices and difficulties in assessing the product. The previous studies mostly saw this problem from the supply side and it can be concluded that there is lack of data and information about the market demand for essential oils. Therefore the aim of this study is to analyze the uncertainty of essential oil as a cosmetic product market. This study tried to answer the central initial problem of market sociology, the constitution of demand. Furthermore, the constitution of demand will discuss about the problem of price and quality assessment of this commodity. Library research was used by the author in this article. The findings shows that the uncertainty problem in the constitution of demand can be seen in the fluctuating price of essential oils and the difficulties faced by experts and non-experts assessing the quality of essential oils. The reason for its difficulties is that the commodities are only assessed from their material qualities. Previous studies about cosmetic and Indonesian Traditional Herbal Medicine (Jamu) and several documents of essential oil reports, will enlarge the constitution of demand side of this essential oil market.